Metal–Electrolyte Solution Dual‐Mode Electrospinning Process for In Situ Fabrication of Electrospun Bilayer Membrane. Issue 20 (23rd August 2020) - Han, Hyeonseok; Hong, Hyeonjun; Park, Sang Min; Kim, Dong Sung
Abstract: Electrospun bilayer membranes comprising two layers, one aligned and the other random, have shown great potential in tissue engineering but previous fabrication processes inevitably relied on manual integration and produced limited types of membranes. Here, a metal–electrolyte solution dual‐mode electrospinning (M‐ELES) for fabrication of electrospun bilayer membrane based on a metal–electrolyte solution switchable collector is developed. The switchable collector enables random nanofiber deposition directly over the preexisting aligned nanofiber layer in an in situ manner and integration of the layers through an on‐demand switch from the metal to the electrolyte solution collector. The electrolyte solution can effectively discharge excessive positive charges of the deposited nanofibers and thus maintain the efficiency of random nanofiber deposition, which allows ≈2.5 times faster fabrication as compared to a conventional method. M‐ELES also possess each layer controllability through on‐demand switching, thereby achieving the electrospun bilayer membranes with diverse physical (e.g., aligned nanofiber density) and mechanical (e.g., maximum tensile load up to ≈3 N) properties. As a biomedical application, in vitro wound healing assay using NIH3T3 cells demonstrates that the electrospun bilayer membrane promotes wound coverage through topographical guidance of the aligned nanofiber layer while providing mechanical support by the random nanofiber layer. Abstract : A metal–electrolyte solution dual‐mode electrospinning (M‐ELES) process is newly suggested as a simple and versatile approach to fabricate an electrospun bilayer membrane comprising two layers, one aligned and the other random, based on a novel metal–electrolyte solution switchable collector. With first discovery on electrical discharging effect of the electrolyte solution, M‐ELES accomplished multifunctional bilayer membrane for various biomedical applications.